Environmentally friendly water-insulating coating
By using core-shell acrylate emulsion and modified Cu-Fe layered bimetallic hydroxide in aqueous coatings, the problem of poor damping and sound insulation performance and antibacterial properties of existing coatings is solved, and the efficient damping and sound insulation and antibacterial effects of the coatings are achieved.
Patent Information
- Application Number
- CN202410796343.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The damping and sound insulation properties and antibacterial properties of existing water-based coatings are poor and need further improvements.
Core-shell acrylate emulsion and modified Cu-Fe layered bimetallic hydroxide are used to design hard core soft shell structures or soft core hard shell structures by changing the ratio of the core layer to the soft and hard monomers in the shell, and modify Cu-Fe layered bimetallic hydroxides through butyl acrylate to enhance their damping performance.
It significantly improves the damping and sound insulation performance and antibacterial properties of the coating, has good room temperature sound insulation performance, and is environmentally friendly, heat-insulating and low VOC.
Smart Images

Figure BDA0004901874020000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, in particular to an environmentally friendly water-insulating coating. Background Art
[0002] Water-based coatings generally include components such as water-based emulsions, defoamers, surfactants, leveling agents, thickeners and additives. The water-based emulsion as a matrix can be selected according to functional requirements. Common ones include styrene-acrylic emulsions, water-acrylic emulsions, silicone-acrylic emulsions, butadiene-styrene emulsions, etc. Compared with oil-based emulsions, water-based emulsions have the advantages of environmental protection and low VOC. Chinese patent CN108624212A discloses a non-toxic and environmentally friendly water-based coating and a preparation method thereof, comprising the following raw materials: polyurethane emulsion, acrylate emulsion, defoamer, surfactant, leveling agent, film-forming aid, thickener, filler, antioxidant, nano α-Al2O3, nano TiO2, and deionized water. The water-based coating of the invention enhances the toughness and adhesion of the coating by adding additives. In addition, the gloss and hardness of the coating are also improved to a certain extent, but the damping sound insulation and antibacterial properties of the coating are poor, and further exploration and improvement are needed. Summary of the invention
[0003] In view of the defects of the prior art, the present invention provides an environmentally friendly water-insulating paint.
[0004] An environmentally friendly water-insulating paint comprises the following raw materials, measured by weight: 70-75 parts of core-shell acrylic emulsion, 1-5 parts of hydroxyethyl cellulose, 0.2-0.5 parts of leveling agent, 0.4-0.8 parts of wetting agent, 0.3-0.5 parts of defoaming agent, 5-6 parts of film-forming agent and 70-75 parts of water.
[0005] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0006] N1: 13-15 parts of methyl methacrylate, 12-13 parts of styrene, 1-2 parts of divinylbenzene and 90-120 parts of water are mixed by mass, and then 1-2 parts of emulsifier and 1-2 parts of Cu-Fe layered double metal hydroxide modified by butyl acrylate are added thereto, and stirred at 200-400r / min in a nitrogen atmosphere at 70-80°C for 20-40min, and finally 0.01-0.05 parts of initiator and 0.2-0.4 parts of sodium bicarbonate are added, and the reaction is continued at a constant temperature for 120-180min to obtain a core emulsion;
[0007] N2: Mix 18-20 parts of butyl acrylate, 15-16 parts of isooctyl acrylate and 0.01-0.05 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 1-2 mL / min in a nitrogen atmosphere at 70-80°C, and continue the reaction for 120-180 min after the addition is completed to obtain a core-shell type acrylate emulsion.
[0008] The present invention firstly adopts methyl methacrylate and styrene to polymerize to prepare acrylic emulsion, which has poor damping effect and does not have good sound insulation performance at room temperature. Furthermore, the present invention uses methyl methacrylate-styrene polymer as the core, and polymerizes butyl acrylate and isooctyl acrylate into the shell to obtain a core-shell acrylic emulsion, whose Tanδ value increases, indicating that its ability to consume sound wave energy is enhanced, and it also has excellent damping performance at room temperature. This is because the modification of the core-shell structure can achieve the purpose of widening the effective damping temperature range by increasing the number of shell layers. The monomer composition of the core layer and the shell layer is different. By changing the ratio of soft and hard monomers in the core layer and the shell layer, the core-shell structure can be designed as a hard core soft shell structure or a soft core hard shell structure. It is precisely because the glass transition temperature of the core layer and the shell layer is different, which effectively makes up for the problem that the effective damping temperature range of a single copolymer is too narrow.
[0009] Furthermore, in the synthesis process of the core-shell structure acrylic emulsion, the present invention mixes the Cu-Fe layered double metal hydroxide and the core material, and polymerizes them together, and its Tanδ value is further increased, and the effective damping temperature range is further widened to the high temperature zone. This is because there are a large number of hydroxyl groups on the surface of the Cu-Fe layered double metal hydroxide, which can form a good connection with the methyl methacrylate-styrene copolymer. Due to the weak van der Waals force between its layers, when the vibration is transmitted, it can consume energy through plane sliding and weaken the transmission of sound waves. Further, the present invention modifies the added Cu-Fe layered double metal hydroxide, and replaces the nitrate ions between its layers with butyl acrylate, and its Tanδ value is increased again, and the effective damping temperature range is widened again, and its sound insulation effect is further enhanced. This is because the interlayer ions of the original Cu-Fe layered double metal hydroxide are nitrate ions, and the Cu-Fe layered double metal hydroxide is connected to the methyl methacrylate-styrene copolymer through the surface hydroxyl groups, and its translation energy consumption is low. After replacing nitrate ions with butyl acrylate, butyl acrylate can also participate in the polymerization of the core emulsion, thereby better transmitting vibration waves. In addition, butyl acrylate is larger than nitrate ions, which further reduces the interlayer force. When the vibration wave is transmitted, it may also move up and down, increase the interlayer distance, and recover under the action of the interlayer force, effectively losing energy. This shows that Cu-Fe layered double hydroxide does have the effect of improving damping performance, but the effect is not obvious. After a series of modifications, it significantly improves the damping performance of the coating.
[0010] In addition, the core-shell structure also has good thermal insulation properties, and the addition of Cu-Fe layered double hydroxide is more conducive to the formation of a thermal insulation layer with good refraction and heat dissipation, thereby enhancing the thermal insulation properties of the coating.
[0011] The preparation method of the butyl acrylate modified Cu-Fe layered double metal hydroxide comprises the following steps:
[0012] S1: adding 18-19 parts of copper nitrate and 24-25 parts of ferric nitrate to 300-400 parts of water by mass, stirring at 200-400 r / min for 5-10 min to obtain a metal salt solution, adding 10-20 parts of sodium citrate and 5-10 parts of urea to the metal salt solution, continuing to stir for 1-2 h, then adjusting the pH of the solution to 10-11 with a 12-16wt% sodium hydroxide aqueous solution, placing at 90-100°C, stirring at 200-400 r / min for reflux reaction for 6-8 h, centrifuging to obtain a precipitate, washing and drying to obtain a Cu-Fe layered double metal hydroxide;
[0013] S2: adding the Cu-Fe layered double metal hydroxide prepared in step S1 to 180-260 parts of anhydrous ethanol, stirring at 200-400 r / min for 24-48 hours in a nitrogen atmosphere, centrifuging at 4000-6000 r / min for 6-10 minutes, taking the supernatant, and obtaining a colloidal solution;
[0014] S3: adding 5-10 parts by mass of butyl acrylate to the colloidal solution prepared in step S2, and then reacting at 90-110° C. for 8-12 hours, cooling to room temperature, and centrifuging at a speed of 10000-12000 r / min for 6-10 minutes, centrifuging to obtain a precipitate, washing, and drying to obtain a Cu-Fe layered double metal hydroxide modified with butyl acrylate.
[0015] The emulsifier is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl alcohol; preferably, the emulsifier is sodium dodecylbenzene sulfonate.
[0016] The initiator is one of sodium persulfate and azobisisobutyronitrile; preferably, the initiator is sodium persulfate.
[0017] Preferably, an environmentally friendly water-insulating coating further comprises 3-5 parts by weight of an antibacterial agent.
[0018] The preparation method of the antibacterial agent comprises the following steps:
[0019] By mass, 2.5-3 parts of IRMOF-8 are added to 50-65 parts of isopropanol and mixed evenly, and then 1.5-2 parts of quaternary ammonium salt-73 are added, and stirred at 75-80° C. in a nitrogen atmosphere at a speed of 150-200 r / min for 1-2 hours. After the stirring, the isopropanol is recovered under reduced pressure to obtain the antibacterial agent.
[0020] Compared with using quaternary ammonium salt-73 alone, the antibacterial agent prepared by the present invention has better antibacterial and mildew-proof durability. This is because IRMOF-8, as a metal organic framework compound, can, on the one hand, play a role in adhering to microorganisms such as bacteria, thereby assisting quaternary ammonium roots and zinc ions in better collaborative sterilization, and on the other hand, it can also enhance the bonding ability with the acrylic emulsion in the coating, thereby achieving long-lasting and efficient antibacterial properties.
[0021] The leveling agent is at least one of carboxymethyl cellulose, silicone oil, and polydimethylsiloxane; preferably, the leveling agent is silicone oil.
[0022] The wetting agent is at least one of propylene glycol, glycerin, Span-80 and Tween-60; preferably, the wetting agent is Span-80.
[0023] The defoamer is at least one of BYK-A555 defoamer and defoamer GP330; preferably, the defoamer is BYK-A555 defoamer.
[0024] The film-forming agent is at least one of dodecyl alcohol ester and hexylene glycol butyl ether acetate; preferably, the film-forming agent is dodecyl alcohol ester.
[0025] The preparation method of the above-mentioned environmentally friendly water-insulating paint comprises the following steps: by weight, 70-75 parts of core-shell acrylic emulsion, 1-5 parts of hydroxyethyl cellulose, 0.2-0.5 parts of leveling agent, 0.4-0.8 parts of wetting agent, 0.3-0.5 parts of defoaming agent, 3-5 parts of antibacterial agent, 5-6 parts of film-forming agent and 70-75 parts of water are mixed, and stirred at a speed of 80-120r / min for 5-15min to obtain the environmentally friendly water-insulating paint.
[0026] Beneficial effects of the invention: The environmentally friendly water-insulating coating of the invention has good damping, sound insulation and antibacterial properties. The core-shell acrylic emulsion is synthesized by modifying the layered double metal hydroxide with butyl acrylate, which enhances its damping performance, has good room temperature sound insulation performance, is environmentally friendly, heat-insulating and low in VOC. DETAILED DESCRIPTION
[0027] Hydroxyethyl cellulose, CAS: 9004-62-0.
[0028] Dodecanol ester, CAS: 25265-77-4.
[0029] Example 1
[0030] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 72 parts of acrylic emulsion, 4 parts of hydroxyethyl cellulose, 0.4 parts of leveling agent, 0.6 parts of wetting agent, 0.4 parts of defoaming agent, 5.6 parts of film-forming agent and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0031] The leveling agent is silicone oil.
[0032] The wetting agent is Span-80.
[0033] The defoamer is BYK-A555 defoamer.
[0034] The film former is dodecyl alcohol ester.
[0035] The preparation method of the acrylic emulsion comprises the following steps: by weight, 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water are mixed, and then 1.5 parts of an emulsifier is added thereto, and the mixture is stirred at a speed of 300 r / min for 30 minutes in a nitrogen atmosphere at 75° C., and finally 0.03 parts of an initiator and 0.3 parts of sodium bicarbonate are added, and the reaction is continued at a constant temperature for 150 minutes to obtain the acrylic emulsion.
[0036] The emulsifier is sodium dodecylbenzene sulfonate.
[0037] The initiator is sodium persulfate.
[0038] Example 2
[0039] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 72 parts of a core-shell acrylic emulsion, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0040] The leveling agent is silicone oil.
[0041] The wetting agent is Span-80.
[0042] The defoamer is BYK-A555 defoamer.
[0043] The film former is dodecyl alcohol ester.
[0044] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0045] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by weight, and then 1.5 parts of emulsifier were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0046] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate and 0.03 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min in a nitrogen atmosphere at 75°C, and continue the reaction for 150 minutes after the addition is completed to obtain a core-shell type acrylate emulsion.
[0047] The emulsifier is sodium dodecylbenzene sulfonate.
[0048] The initiator is sodium persulfate.
[0049] Example 3
[0050] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 72 parts of a core-shell acrylic emulsion, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0051] The leveling agent is silicone oil.
[0052] The wetting agent is Span-80.
[0053] The defoamer is BYK-A555 defoamer.
[0054] The film former is dodecyl alcohol ester.
[0055] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0056] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by mass, and then 1.5 parts of emulsifier and 1.6 parts of Cu-Fe layered double metal hydroxide were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0057] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate and 0.03 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min in a nitrogen atmosphere at 75°C, and continue the reaction for 150 minutes after the addition is completed to obtain a core-shell type acrylate emulsion.
[0058] The emulsifier is sodium dodecylbenzene sulfonate.
[0059] The initiator is sodium persulfate.
[0060] The preparation method of the Cu-Fe layered double metal hydroxide comprises the following steps: adding 18.7 parts of copper nitrate and 24.1 parts of ferric nitrate to 300 parts of water by mass, stirring at 300 r / min for 10 minutes to obtain a metal salt solution, adding 15 parts of sodium citrate and 8 parts of urea to the metal salt solution, continuing to stir for 2 hours, then adjusting the pH value of the solution to 10.5 with a sodium hydroxide aqueous solution with a concentration of 14wt%, placing the solution at 95°C, stirring and refluxing at a speed of 300 r / min for 8 hours, taking out a precipitate by centrifugation, washing and drying, and obtaining the Cu-Fe layered double metal hydroxide.
[0061] Example 4
[0062] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 72 parts of a core-shell acrylic emulsion, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0063] The leveling agent is silicone oil.
[0064] The wetting agent is Span-80.
[0065] The defoamer is BYK-A555 defoamer.
[0066] The film former is dodecyl alcohol ester.
[0067] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0068] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by mass, and then 1.5 parts of emulsifier and 1.6 parts of Cu-Fe layered double metal hydroxide modified by butyl acrylate were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0069] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate and 0.03 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min in a nitrogen atmosphere at 75°C, and continue the reaction for 150 minutes after the addition is completed to obtain a core-shell type acrylate emulsion.
[0070] The emulsifier is sodium dodecylbenzene sulfonate.
[0071] The initiator is sodium persulfate.
[0072] The preparation method of the butyl acrylate modified Cu-Fe layered double metal hydroxide comprises the following steps:
[0073] S1: 18.7 parts of copper nitrate and 24.1 parts of ferric nitrate were added to 300 parts of water by mass, and stirred at 300 r / min for 10 min to obtain a metal salt solution. 15 parts of sodium citrate and 8 parts of urea were added to the metal salt solution, and stirring was continued for 2 h. Then, the pH of the solution was adjusted to 10.5 with a 14 wt% sodium hydroxide aqueous solution, and the solution was placed at 95°C and stirred at 300 r / min for 8 h. The precipitate was centrifuged, washed and dried to obtain a Cu-Fe layered double metal hydroxide.
[0074] S2: adding the Cu-Fe layered double metal hydroxide prepared in step S1 to 200 parts of anhydrous ethanol, stirring at 300 r / min for 24 h in a nitrogen atmosphere, centrifuging at 4000 r / min for 10 min, taking the supernatant, and obtaining a colloidal solution;
[0075] S3: adding 7 parts by mass of butyl acrylate to the colloidal solution prepared in step S2, and then reacting at 100° C. for 10 hours, cooling to room temperature, and centrifuging at a speed of 12000 r / min for 6 minutes, centrifuging and collecting the precipitate, washing and drying to obtain a Cu-Fe layered double metal hydroxide modified with butyl acrylate.
[0076] Example 5
[0077] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 72 parts of a core-shell acrylic emulsion, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0078] The leveling agent is silicone oil.
[0079] The wetting agent is Span-80.
[0080] The defoamer is BYK-A555 defoamer.
[0081] The film former is dodecyl alcohol ester.
[0082] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0083] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by weight, and then 1.5 parts of emulsifier were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0084] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate, 1.6 parts of butyl acrylate-modified Cu-Fe layered double metal hydroxide, and 0.03 parts of initiator, by mass, to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min in a nitrogen atmosphere at 75°C, and continue the reaction for 150 min after the addition is completed to obtain a core-shell type acrylate emulsion.
[0085] The emulsifier is sodium dodecylbenzene sulfonate.
[0086] The initiator is sodium persulfate.
[0087] The preparation method of the butyl acrylate modified Cu-Fe layered double metal hydroxide comprises the following steps:
[0088] S1: 18.7 parts of copper nitrate and 24.1 parts of ferric nitrate were added to 300 parts of water by mass, and stirred at 300 r / min for 10 min to obtain a metal salt solution. 15 parts of sodium citrate and 8 parts of urea were added to the metal salt solution, and stirring was continued for 2 h. Then, the pH of the solution was adjusted to 10.5 with a 14 wt% sodium hydroxide aqueous solution, and the solution was placed at 95°C and stirred at 300 r / min for 8 h. The precipitate was centrifuged, washed and dried to obtain a Cu-Fe layered double metal hydroxide.
[0089] S2: adding the Cu-Fe layered double metal hydroxide prepared in step S1 to 200 parts of anhydrous ethanol, stirring at 300 r / min for 24 h in a nitrogen atmosphere, centrifuging at 4000 r / min for 10 min, taking the supernatant, and obtaining a colloidal solution;
[0090] S3: adding 7 parts by mass of butyl acrylate to the colloidal solution prepared in step S2, and then reacting at 100° C. for 10 hours, cooling to room temperature, and centrifuging at a speed of 12000 r / min for 6 minutes, centrifuging and collecting the precipitate, washing and drying to obtain a Cu-Fe layered double metal hydroxide modified with butyl acrylate.
[0091] Example 6
[0092] A method for preparing an environmentally friendly water-insulating water-soluble paint comprises the following steps: by weight, 70.4 parts of a core-shell acrylic emulsion, 1.6 parts of a Cu-Fe layered double metal hydroxide modified by butyl acrylate, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating water-soluble paint.
[0093] The leveling agent is silicone oil.
[0094] The wetting agent is Span-80.
[0095] The defoamer is BYK-A555 defoamer.
[0096] The film former is dodecyl alcohol ester.
[0097] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0098] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by weight, and then 1.5 parts of emulsifier were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0099] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate and 0.03 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min in a nitrogen atmosphere at 75°C, and continue the reaction for 150 minutes after the addition is completed to obtain a core-shell type acrylate emulsion.
[0100] The emulsifier is sodium dodecylbenzene sulfonate.
[0101] The initiator is sodium persulfate.
[0102] The preparation method of the butyl acrylate modified Cu-Fe layered double metal hydroxide comprises the following steps:
[0103] S1: 18.7 parts of copper nitrate and 24.1 parts of ferric nitrate were added to 300 parts of water by mass, and stirred at 300 r / min for 10 min to obtain a metal salt solution. 15 parts of sodium citrate and 8 parts of urea were added to the metal salt solution, and stirring was continued for 2 h. Then, the pH of the solution was adjusted to 10.5 with a 14 wt% sodium hydroxide aqueous solution, and the solution was placed at 95°C and stirred at 300 r / min for 8 h. The precipitate was centrifuged, washed and dried to obtain a Cu-Fe layered double metal hydroxide.
[0104] S2: adding the Cu-Fe layered double metal hydroxide prepared in step S1 to 200 parts of anhydrous ethanol, stirring at 300 r / min for 24 h in a nitrogen atmosphere, centrifuging at 4000 r / min for 10 min, taking the supernatant, and obtaining a colloidal solution;
[0105] S3: adding 7 parts by mass of butyl acrylate to the colloidal solution prepared in step S2, and then reacting at 100° C. for 10 hours, cooling to room temperature, and centrifuging at a speed of 12000 r / min for 6 minutes, centrifuging and collecting the precipitate, washing and drying to obtain a Cu-Fe layered double metal hydroxide modified with butyl acrylate.
[0106] Example 7
[0107] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 70.4 parts of a core-shell acrylic emulsion, 1.6 parts of a Cu-Fe layered double metal hydroxide, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0108] The leveling agent is silicone oil.
[0109] The wetting agent is Span-80.
[0110] The defoamer is BYK-A555 defoamer.
[0111] The film former is dodecyl alcohol ester.
[0112] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0113] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by weight, and then 1.5 parts of emulsifier were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0114] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate and 0.03 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min, and continue the reaction for 150 min after the addition is completed to obtain a core-shell type acrylate emulsion.
[0115] The emulsifier is sodium dodecylbenzene sulfonate.
[0116] The initiator is sodium persulfate.
[0117] The preparation method of the Cu-Fe layered double metal hydroxide comprises the following steps:
[0118] By mass, 18.7 parts of copper nitrate and 24.1 parts of ferric nitrate were added to 300 parts of water, and stirred at 300 r / min for 10 min to obtain a metal salt solution. 15 parts of sodium citrate and 8 parts of urea were added to the metal salt solution, and stirring was continued for 2 h. Then, the pH of the solution was adjusted to 10.5 with a 14 wt% sodium hydroxide aqueous solution, and the solution was placed at 95°C and stirred at 300 r / min for reflux reaction for 8 h. The precipitate was taken out by centrifugation, washed and dried to obtain a Cu-Fe layered double metal hydroxide.
[0119] Example 8
[0120] A method for preparing an environmentally friendly water-insulating paint comprises the following steps: by weight, 72 parts of a core-shell acrylic emulsion, 4 parts of hydroxyethyl cellulose, 0.4 parts of a leveling agent, 0.6 parts of a wetting agent, 0.4 parts of a defoaming agent, 3.2 parts of an antibacterial agent, 5.6 parts of a film-forming agent, and 72 parts of water are mixed, and stirred at a speed of 100 r / min for 10 minutes to obtain the environmentally friendly water-insulating paint.
[0121] The leveling agent is silicone oil.
[0122] The wetting agent is Span-80.
[0123] The defoamer is BYK-A555 defoamer.
[0124] The film former is dodecyl alcohol ester.
[0125] The preparation method of the antibacterial agent comprises the following steps:
[0126] By mass, 2.6 parts of IRMOF-8 (CAS: 473981-43-0) were added to 60 parts of isopropanol and mixed evenly, and then 1.7 parts of quaternary ammonium salt-73 (CAS: 15763-48-1) were added, and stirred at 78° C. in a nitrogen atmosphere at a speed of 180 r / min for 1.5 hours. After the stirring, the isopropanol was recovered under reduced pressure to obtain the antibacterial agent.
[0127] The preparation method of the core-shell type acrylic emulsion comprises the following steps:
[0128] N1: 14 parts of methyl methacrylate, 12.3 parts of styrene, 1.4 parts of divinylbenzene and 100 parts of water were mixed by mass, and then 1.5 parts of emulsifier and 1.6 parts of Cu-Fe layered double metal hydroxide modified by butyl acrylate were added thereto, and stirred at 300 r / min for 30 minutes in a nitrogen atmosphere at 75°C, and finally 0.03 parts of initiator and 0.3 parts of sodium bicarbonate were added, and the reaction was continued at a constant temperature for 150 minutes to obtain a core emulsion;
[0129] N2: Mix 19 parts of butyl acrylate, 15.5 parts of isooctyl acrylate and 0.03 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 2 mL / min in a nitrogen atmosphere at 75°C, and continue the reaction for 150 minutes after the addition is completed to obtain a core-shell type acrylate emulsion.
[0130] The emulsifier is sodium dodecylbenzene sulfonate.
[0131] The initiator is sodium persulfate.
[0132] The preparation method of the butyl acrylate modified Cu-Fe layered double metal hydroxide comprises the following steps:
[0133] S1: 18.7 parts of copper nitrate and 24.1 parts of ferric nitrate were added to 300 parts of water by mass, and stirred at 300 r / min for 10 min to obtain a metal salt solution. 15 parts of sodium citrate and 8 parts of urea were added to the metal salt solution, and stirring was continued for 2 h. Then, the pH of the solution was adjusted to 10.5 with a 14 wt% sodium hydroxide aqueous solution, and the solution was placed at 95°C and stirred at 300 r / min for 8 h. The precipitate was centrifuged, washed and dried to obtain a Cu-Fe layered double metal hydroxide.
[0134] S2: adding the Cu-Fe layered double metal hydroxide prepared in step S1 to 200 parts of anhydrous ethanol, stirring at 300 r / min for 24 h in a nitrogen atmosphere, centrifuging at 4000 r / min for 10 min, taking the supernatant, and obtaining a colloidal solution;
[0135] S3: adding 7 parts by mass of butyl acrylate to the colloidal solution prepared in step S2, and then reacting at 100° C. for 10 hours, cooling to room temperature, and centrifuging at a speed of 12000 r / min for 6 minutes, centrifuging and collecting the precipitate, washing and drying to obtain a Cu-Fe layered double metal hydroxide modified with butyl acrylate.
[0136] The antibacterial performance of the environmentally friendly water-insulating paint of Example 8 was tested using the method in HG / T3950-2007, and the antibacterial rate (Staphylococcus aureus, Escherichia coli) reached more than 90%, and the mold growth level was level 0.
[0137] Test Example 1
[0138] The environmentally friendly water-insulating coating prepared in each embodiment was poured into a template, dried naturally at room temperature for 48 hours, and then placed in an oven at 60° C. for 24 hours to prepare a 20 mm×6.50 mm×1.50 mm specimen.
[0139] The damping performance of the environmentally friendly water-insulating coating prepared in the embodiment is tested using a DMTAQ800 dynamic mechanical properties instrument. During the test, the following settings are set: the tensile mode is selected, the strain condition is 1% strain, the test frequency is 1 Hz, the temperature range is set at -100-60°C during the test, and the temperature increase rate is 3°C per minute.
[0140] Table 1: DMA test data
[0141]
[0142] The loss factor (Tanδ) is usually used to represent the damping performance of a material. The larger the Tanδ value, the better the damping performance of the material. Correspondingly, the greater the material's ability to absorb and consume sound vibration energy. Materials with Tanδ≥0.3 are all effective damping materials.
[0143] As shown in Table 1, Example 1 uses core materials to directly make acrylic emulsion, and its Tanδ value is the smallest, and its effective damping temperature range is between -46.8 and 13.4, which shows that its damping effect is the worst and it does not have good sound insulation performance at room temperature. Example 2 makes the acrylic emulsion into a core-shell structure, and its Tanδ value increases, and its effective damping temperature range is between -47.8 and 35.2, which shows that its ability to consume sound wave energy is enhanced, and it also has excellent damping performance at room temperature. This is because the modification of the core-shell structure can achieve the purpose of widening the effective damping temperature range by increasing the number of shell layers. The monomer composition of the core layer and the shell layer is different. By changing the ratio of soft and hard monomers in the core layer and the shell layer, the core-shell structure can be designed as a hard core soft shell structure or a soft core hard shell structure. It is precisely because the glass transition temperature of the core layer and the shell layer is different, which effectively compensates for the problem that the effective damping temperature range of a single copolymer is too narrow. Example 3 In the synthesis process of the core-shell structure acrylic emulsion, the Cu-Fe layered double metal hydroxide and the core material are mixed and co-polymerized, and the Tanδ value is further increased, and the effective damping temperature range is -46.6-38.3. This is because there are a large number of hydroxyl groups on the surface of the Cu-Fe layered double metal hydroxide, which can form a good connection with the methyl methacrylate-styrene copolymer. Due to the weaker van der Waals force between its layers, when the vibration is transmitted, it can consume energy through plane sliding and weaken the transmission of sound waves. Example 4 Further modify the added Cu-Fe layered double metal hydroxide, and use butyl acrylate to replace the nitrate ions between its layers, and its Tanδ value is increased again, and the effective damping temperature range is -48.1-42.7, and its sound insulation effect is further enhanced. This is because the interlayer ions of the original Cu-Fe layered double metal hydroxide are nitrate ions, and the Cu-Fe layered double metal hydroxide is connected to the methyl methacrylate-styrene copolymer through the surface hydroxyl groups, and its translation energy consumption is low. After replacing the nitrate ions with butyl acrylate, butyl acrylate can also participate in the polymerization of the core emulsion, thereby better transmitting the vibration wave, and butyl acrylate is larger than the nitrate ion, which further reduces the interlayer force, and may also move up and down when the vibration wave is transmitted, and the fluctuation increases the interlayer distance, and recovers under the action of the interlayer force, effectively losing energy. Example 5 attempts to add butyl acrylate-modified Cu-Fe layered double metal hydroxide to the shell raw material, and finds that its performance is slightly lower than that added to the core. The present invention believes that this is due to the larger volume of the Cu-Fe layered double metal hydroxide, which destroys the generation of the core-shell structure, thereby causing its damping performance to decrease. Example 6 and Example 7 attempt to add Cu-Fe layered double metal hydroxide and butyl acrylate-modified Cu-Fe layered double metal hydroxide directly to environmentally friendly water-insulating coatings, and find that its damping performance is slightly improved compared to Example 2 without adding, but significantly lower than Example 4.This shows that Cu-Fe layered double hydroxide does have the effect of improving damping performance, but the effect is not obvious. After a series of modifications, the damping performance of the coating is significantly improved.
[0144] Test Example 2
[0145] The environmentally friendly water-insulating paint is applied on the tinplate. After it dries, a layer of adhesive is applied on the coating surface. The circular forging die of the adhesion tester is connected to the coating surface through the adhesive. After the adhesive dries for 24 hours, the excess coating is scraped off along the periphery of the circular forging die. The adhesion tester is used to give the circular forging die a lifting force. When the circular forging die pulls the coating away from the tinplate surface, the displayed value is F. max , the area of the circular forging die is S, the final result is measured three times and the average value is taken. The adhesion calculation formula is as follows:
[0146] Adhesion (MPa) = F max / S
[0147] Table 2: Paint adhesion test results
[0148] Adhesion(MPa) Example 1 0.56 Example 2 0.75 Example 3 0.81 Example 4 1.01 Example 5 1.05 Example 6 0.79 Example 7 0.76
[0149] It can be seen from Table 2 that the changes in adhesion and Tanδ values of the environmentally friendly coatings obtained in Examples 1 to 7 are basically consistent. This shows that the Cu-Fe layered double metal hydroxide also has the effect of improving the adhesion of the coating. This is because there are a large number of hydroxyl groups on the surface of the Cu-Fe layered double metal hydroxide, which can form a good connection with the methyl methacrylate-styrene copolymer, and the copper ions and iron ions on its layer have a strong chelating effect, which can chelate with the groups on the surface of the tinplate, thereby enhancing the force between the coating and the metal surface. Therefore, Example 5 adds butyl acrylate-modified Cu-Fe layered double metal hydroxide to the shell raw material, and its adhesion is slightly higher than that of Example 4, which adds butyl acrylate-modified Cu-Fe layered double metal hydroxide to the core, but the damping performance of Example 5 is significantly lower than that of Example 4.
Claims
1. Environmentally friendly water-insulating paint, characterized in that: The raw materials include, by weight: 70-75 parts of core-shell acrylic emulsion, 1-5 parts of hydroxyethyl cellulose, 0.2-0.5 parts of leveling agent, 0.4-0.8 parts of wetting agent, 0.3-0.5 parts of defoaming agent, 3-5 parts of antibacterial agent, 5-6 parts of film-forming agent, and 70-75 parts of water; The preparation method of the core-shell type acrylic emulsion comprises the following steps: N1: Mix 13-15 parts of methyl methacrylate, 12-13 parts of styrene, 1-2 parts of divinylbenzene and 90-120 parts of water by mass, then add 1-2 parts of emulsifier and 1-2 parts of Cu-Fe layered double metal hydroxide modified by butyl acrylate, stir for 20-40 minutes in a nitrogen atmosphere at 70-80°C, finally add 0.01-0.05 parts of initiator and 0.2-0.4 parts of sodium bicarbonate, continue the isothermal reaction for 120-180 minutes, and obtain a core emulsion; N2: Mix 18-20 parts of butyl acrylate, 15-16 parts of isooctyl acrylate and 0.01-0.05 parts of initiator by mass to obtain a shell monomer emulsion; add the shell monomer emulsion dropwise to the core emulsion obtained in step N1 at a rate of 1-2 mL / min in a nitrogen atmosphere at 70-80° C., and continue the reaction for 120-180 min after the addition is completed to obtain a core-shell type acrylate emulsion; The preparation method of the butyl acrylate modified Cu-Fe layered double metal hydroxide comprises the following steps: S1. By mass, add 18-19 parts of copper nitrate and 24-25 parts of ferric nitrate to 300-400 parts of water, stir for 5-10 minutes to obtain a metal salt solution, add 10-20 parts of sodium citrate and 5-10 parts of urea to the metal salt solution, continue stirring for 1-2 hours, adjust the pH of the solution to 10-11, place it at 90-100°C and stir under reflux for 6-8 hours, centrifuge to obtain a precipitate, wash and dry it, and obtain a Cu-Fe layered double metal hydroxide; S2: adding the Cu-Fe layered double metal hydroxide prepared in step S1 to 180-260 parts of anhydrous ethanol, stirring for 24-48 hours in a nitrogen atmosphere, centrifuging, and taking the supernatant to obtain a colloidal solution; S3: Add 5-10 parts by mass of butyl acrylate to the colloidal solution prepared in step S2, and then react at 90-110° C. for 8-12 hours, cool to room temperature, centrifuge to obtain a precipitate, wash and dry to obtain a butyl acrylate-modified Cu-Fe layered double metal hydroxide.
2. The environmentally friendly water-insulating coating according to claim 1, characterized in that: The preparation method of the antibacterial agent comprises the following steps: adding 2.5-3 parts of IRMOF-8 to 50-65 parts of isopropanol by mass and mixing them evenly, then adding 1.5-2 parts of quaternary ammonium salt-73, stirring for 1-2 hours in a nitrogen atmosphere at 75-80° C., and recovering the isopropanol under reduced pressure after the stirring to obtain the antibacterial agent.
3. The environmentally friendly water-insulating paint according to claim 1, characterized in that: The emulsifier is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl alcohol.
4. The environmentally friendly water-insulating paint according to claim 1, characterized in that: The initiator is one of sodium persulfate and azobisisobutyronitrile.
5. The environmentally friendly water-insulating paint according to claim 1, characterized in that: The leveling agent is at least one of carboxymethyl cellulose and silicone oil.
6. The environmentally friendly water-insulating paint according to claim 1, characterized in that: The wetting agent is at least one of propylene glycol, glycerin, Span-80 and Tween-60.
7. The environmentally friendly water-insulating paint according to claim 1, characterized in that: The defoamer is at least one of BYK-A555 defoamer and defoamer GP330.
8. The environmentally friendly water-insulating paint according to claim 1, characterized in that: The film-forming agent is at least one of lauryl alcohol ester and hexanediol butyl ether acetate.
Citation Information
Patent Citations
Non-toxic environmental-friendly aqueous coating and preparation method thereof
CN108624212A
Antibacterial and mildew-proof coating with good weather resistance
CN111234691A
Building coating and preparation method thereof
CN116535927A